IMF Survey : Volume 29, Issue 23. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2000)
Jack Boorman has been Director of the IMF's Policy Development and Review (PDR) Department since August 1990. PDR plays a central role in the design, implementation, and evaluation of IMF policies relating to surveillance and the use of IMF financing, including concessional financing for low-income countries. Boorman met recently with the IMF Survey to discuss the important progress being made in the area of debt relief for heavily indebted developing countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet